Usutu virus: An emerging flavivirus with potential threat to public health in Africa: Nigeria as a case study - Akinsulie, Olalekan Chris; Adesola, Ridwan Olamilekan; Bakre, Adetolase; Adebowale, Oluwawemimo Oluseun; Adeleke, Richard; Ogunleye, Seto Charles; Oladapo, Ifeoluwa Peace (Frontiers in Veterinary Science, 2023)
Usutu virus (USUV) is an arthropod-borne virus (arbovirus) of the Flaviviridae family (genus Flavivirus) which belong to the Japanese encephalitis virus complex. Culex mosquitoes have been implicated in the transmission of this pathogen. The major susceptible hosts of USUV are migratory birds, thereby potentiating their ability to spread from one region to another globally. Nigeria has the largest economy in Africa with a significant percentage of the gross domestic product relying on the agricultural and animal production industry. This review explores the zoonotic potentials of the virus in Africa, especially Nigeria, with a special focus on the devastating sequelae this might lead to in the future if necessary precautionary policies are not enacted and adopted to bolster the surveillance system for mosquito-borne viruses.